Traffic Surveillance System - Asnani, Y.P; Paryani, J.P; Meshram, P.A (International Journal of Computer Sciences and Engineering, 2025)
Due to the large number of vehicles in circulation, studies of intelligent traffic systems have increased. Most of studies focus on the detection, tracking and counting of vehicles and on the estimation of traffic parameters. Two wheelers are the most important mode of transport in many countries. The main advantages of motorcycles are their low price and operation cost compared with other vehicles. But the number of accidents involving motorcycles has increased during the last decade and no proper database maintenance is provided. Thus, our paper provides a survey on various techniques into use for improving traffic conditions and for avoiding accidents. It suggests techniques for data collection using various implemented methods.